2021
DOI: 10.18502/jebhpme.v5i4.8158
|View full text |Cite
|
Sign up to set email alerts
|

The Deadly Nature of the Virus Depression: Iranian Medical Staff Battling COVID-19

Abstract: Background: COVID-19, which began in December 2019 in China, can have a broader impact on individuals' mental dimensions. Meanwhile, the medical staff battling this epidemic are more at risk of mental and emotional problems.  This study aimed to examine the level of stress, anxiety, and depression and their relationship with the level of knowledge of medical staff battling in COVID-19 pandemic treatment. Methods: This descriptive-analytical study was conducted on 641 medical staff using an online platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This reported prevalence is higher than that of the general population which has been reported to be 29.7% in the same time period ( 49 ). This finding is similar to a number of international ( 7 , 9 11 ) and national ( 16 20 ) studies conducted at the time of the COVID-19 pandemic for assessing psychological distress and mental health problems among healthcare workers which have reported a high prevalence of anxiety and depression. One similar study performed a year earlier among healthcare workers from twelve different cities in India revealed that 52.9% of the participants had the risk of psychological distress that needed further evaluation ( 50 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This reported prevalence is higher than that of the general population which has been reported to be 29.7% in the same time period ( 49 ). This finding is similar to a number of international ( 7 , 9 11 ) and national ( 16 20 ) studies conducted at the time of the COVID-19 pandemic for assessing psychological distress and mental health problems among healthcare workers which have reported a high prevalence of anxiety and depression. One similar study performed a year earlier among healthcare workers from twelve different cities in India revealed that 52.9% of the participants had the risk of psychological distress that needed further evaluation ( 50 ).…”
Section: Discussionsupporting
confidence: 88%
“…Studies have also shown high rates of anxiety and depression among Iranian healthcare workers in the COVID-19 pandemic ( 16 18 ), especially among the female ( 19 ). Iranian studies have shown negative psychological experiences caused by COVID-19 in healthcare workers, such as fatigue, discomfort, and helplessness due to high-intensity work, anxiety, and worry about family members ( 20 ). An Iranian study performed by Jalili et al ( 21 ) have reported high levels of burnout among 53% of the healthcare workers in the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%